Cournot Meets Bayes-Nash: A Discontinuity in Behavior in Finitely Repeated Duopoly Games - Cédric Argenton; Radosveta Ivanova-Stenzel; Wieland Müller (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
We conduct a series of Cournot duopoly market experiments with a high number of repetitions and fixed matching. Our treatments include markets with (a) complete cost symmetry and complete information, (b) slight cost asymmetry and complete information, and (c) varying cost asymmetries and incomplete information. For the case of complete cost symmetry and complete information, our data confirm the well-known result that duopoly players achieve, on average, partial collusion. However, as soon as any level of cost asymmetry or incomplete information is introduced, observed average individual quantities are remarkably close to the static Bayes-Nash equilibrium predictions.
Keywords: D43; L13; C72; C92; 330; Cournot; Bayesian game; Bayes-Nash equilibrium; repeated games; collusion; cooperation; experimental economics